Banking credit restructuring in Indonesia: Quo vadis? - Dendy Indramawan (Jurnal Inovasi Ekonomi, 2021)
This research aims to analyze the impact of Coronavirus Disease (Covid-19) on the accounting practices in banks associated with Indonesian Financial Accounting Standards (PSAK) 71 – Financial Instrument, particularly the allowance for impairment losses (CKPN) to respond to the Indonesian Financial Service Authority's Regulation (POJK) Number: 11/POJK.03/2020 concerning credit restructuring program and quality assets assessment. The research methodology is triangulation. This study reveals that the restructuring program helps banks from a significant jump of weak quality credits. Banks need to analyze the recovery rate of debtors as a basis for the stage of PSAK 71 with the Expected Credit Loss approach. The higher the CKPN, the smaller the net income. Besides, a tremendous amount of CKPN will pressure the Capital Adequacy Ratio (CAR). Therefore, shareholders should increase the capital, or the Indonesian Financial Service Authority (OJK) forces the bank(s) into a merger or acquisition.